Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Prostitution et immigration des femmes latino-américaines en Espagne - Oso Casas, Laura (Cahiers du Genre, 2006)
L’objectif de cet article est de montrer qu’une bonne partie des femmes latino-américaines, contrairement à l’image souvent mise en avant de la femme objet de trafic, ont pris la décision de migrer en étant conscientes de l’activité qu’elles allaient pratiquer en Espagne. Cependant, bien qu’elles puissent opter volontairement pour le « travail » sexuel, devenant les principales pourvoyeuses économiques des foyers transnationaux (actrices de la migration, actrices économiques et du développement), elles sont prises dans plusieurs circuits qui contribuent à la reproduction des inégalités sociales. Ces circuits sont sous-tendus par l’articulation de plusieurs facteurs : la circulation des personnes, la mobilité des prostituées, la pression du foyer transnational, l’irrégularité juridique, ainsi que l’inégalité de genre.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique centrale; amérique du sud; amériques; approches et analyses; cours; discipline; espagne; europe; immigration; inégalités; migration; postmodernisme; premier cycle; prostitution; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

La métamorphose impensable: essai sur le transsexualisme et l'identité personnelle - Castel, Pierre-Henri (Gallimard, 2003)
Être un homme ou une femme est-il naturel ou culturel ? L'identité sexuelle s'enracine-t-elle dans le corps, est-ce un donné physiologique, voire neurobiologique ? Ou ne s'agit-il que d'un rôle qu'on joue, qu'on pourrait intervertir avec d'autres et dont on puisse altérer le texte ? La métamorphose transsexuelle est une voie d'accès privilégiée à ces interrogations, parce que le réel de l'identité, avant d'avoir pu dire son mot, est ici forcé par un fabuleux acte autoconstructif : si tant de magistrats, tant de psychiatres sont embarrassés par les transsexuels, si leur affaire est à la pointe avancée de la bioéthique, de la critique de la culture ou de la protestation libertaire, c'est justement parce qu'ils assument leur identité comme une «construction sociale». Dans la sphère éthérée des débats savants, ils font sentir l'urgence d'une affaire de vie ou de mort, en un court-circuit inattendu entre une question de catégorisation et une atteinte directe à la chair. Le problème est, pour le dire d'un mot, métaphysique. Il vise le nœud obscur qui attache ce corps à ce je ; il oblige donc à dévoiler quelle nature humaine il faut, à un moment ou à un autre, nous supposer. Et il est à peine besoin de l'approfondir pour que la philosophie, la psychanalyse, mais aussi la médecine, la sociologie, le droit - toutes disciplines aspirant à sauver leur rationalité, voire leur scientificité, face à ce qui paraît la déraison même, «changer de sexe» - en ressortent ébranlés. Telle est la crise des certitudes qui motive cet essai.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; transféminisme

L'invention de l'hétérosexualité - Katz, Jonathan (Grands classiques de l'érotologie moderne, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art